Consultant Identification on Critical Risk Factors Affecting Construction Project Execution in Ghana - Agyeman Junior, Atta; Adu Gyamfi, Timothy; Akorli, King Solomon (Advances in Social Sciences Research Journal, 2017)
The consultants are front liners in execution of construction project and their perceived critical risk factors affecting construction project delivery is wealth considered and being aware to such hindrance will ensure efficient and effective project management technique to manage such risk should it occur. The purpose of the study was to identify critical risk factors affecting construction project delivery in Ghana. The study objective was to identify consultant’s perception on critical risk factors hindering construction execution and how to manage the risk. The study adopted a quantitative approach involving a cross-sectional design using survey, questionnaires administered to a population of 355 consultants of the Ghana Consulting Engineering Association (GCEA). Descriptive statistics, cross tabulations, factor analysis were used to analyse the resulting data. The study found that the most critical risk factors hindering construction delivery included high performance expectations, tight project schedule, poor program planning, excessive approval procedures, and bureaucracy of government. The study has establish that For all government funded projects, the main financial risk was the delay in payment and bankruptcy of stakeholders and main source of time overrun risks was enlargement of the project scope. The study further shown that the management of time schedule risk and financial risk included setting and agreeing on reasonable time lines , prompt payments on the part of stakeholders and obtaining reliable source of project funding, government to reduce the interest rates in order for stakeholders in construction projects to secure loans to fund projects respectively.